Nanopatterning Au chips for SPR refractometer by using interference lithography and chalcogenide photoresist - Dan’ko, V.A.; Dorozinsky, G.V.; Indutnyi, I.Z.; Myn’ko, V.I.; Ushenin, Yu.V.; Shepeliavyi, P.E.; Lukaniuk, M.V.; Korchovyi, A.A.; Khrystosenko, R.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
This study reports on development of the interference lithography (IL) technique applying the resist based on chalcogenide glass films for fabrication of gold chips in the nform of periodic surface nanostructures for surface plasmon resonance (SPR) refractometers. The IL technique was optimized for patterning the Au layers and formation of one-dimensional (grating) structures with the spatial frequency close to 3300 mm⁻¹. The spatial frequency and depth of grating grooves were selected with account of the condition for Bragg reflection of plasmons at the operation wavelength of SPR refractometer and given environment (which is a condition for enhancing biosensor sensitivity as compared to that of a flat Au chip surface). It has experimentally been demonstrated that the use of diffraction patterns in SPR sensor increases its response by 17%.